Juridical Analysis of the Problem of Land Acquisition Compensation for the Development of the Jakarta – Cikampek II Toll Road Southside III - Nur Amany Burhan; Suardi Suardi (LEGAL BRIEF, 2022)
The issue that frequently happens in regards to the process of land acquisition for the public interest is in determining the amount of compensation. This problem often arises because the community or landowner asks for a higher price of compensation while the government can only offer it based on the price determined by the land appraiser. Many people or landowners complain about compensation, especially the compensation assessment factor which is carried out without paying attention to fairness and feasibility. The number of complaints regarding the compensation has resulted in the filing of an objection in court. One example of a case concerning the issue of determining compensation occurs regarding land acquisition that occurs in the community, namely the case of court decision number 15/Pdt.G/2021/PN BKS. This research aims to analyze how the implementation of land procurement compensation determination and what is the judge's consideration in the matter of objection to land acquisition compensation based on the decision of the district court number 15/Pdt.G/2021/PN Bks. The type of research used by the author in this research is normative juridical by examining library materials or secondary data and the application of positive legal rules.